Establishing key factors towards implementing integrated Building Information Modeling (BIM) in AEC industry: Malaysia study - AlMashjary, Badr M.; Umi Kalsum Zolkafli @ Zulkifly; Asrul Sani Abdul Razak (Penerbit Universiti Kebangsaan Malaysia, 2020)
Building information modeling (BIM) is a systemic approach that enhances the effectiveness and overall quality of construction projects. Integrated BIM (iBIM) is an advanced state of BIM that integrates and synchronizes disparate project data in a centralized database of reliable, accessible and real-time project information. The purpose of this paper is to investigate key factors of iBIM implementation by AEC industry players within the Malaysian context. This study adopted a quantitative method. A questionnaire survey is conducted in Kuala Lumpur, Malaysia, to collect data using 5-level Likert scale questions. The study population was AEC industry players working in firms affiliated with professional institutes in Malaysia. The one-sample T-test and Descriptive Statistics are employed to rank the key factors of iBIM implementation in construction projects. The data were analysed by Statistical Package for the Social Science SPSS software version 20 and Microsoft Excel. It is found that policy factors are the statistically significant factors affecting iBIM implementation in Malaysian construction projects followed by interoperability; learning and education; and finally standardization. Key factors are important as a reference or guideline in advance of selecting the most appropriate framework for achieving successful iBIM implementation in AEC industry.